“Pugnas Renhidas”: Futebol, Cultura e Sociedade em Salvador, 1901 - 1924 - Santos, Henrique Sena dos (2012)
This present work deals the presence and developing of the football at Salvador between 1901 – 1924. This text analyzes how the different subjects who lived in that city were related with the practice, which expectations had about it and how the specifics of the pos-abolition and republican context influenced in the relationship of men and women with the game. From various printed sources it was analyzed the emergence of clubs and foot-ball leagues by the elites, middle and popular layers as well as the representations, practices and appropriations that were subject to those elements. Finally football in this work was conceived as a practice of building, confrontation and assimilation of social, cultural and racial identities.